2020
DOI: 10.3389/fpsyg.2020.00092
|View full text |Cite
|
Sign up to set email alerts
|

Contributions From Psychology to Effectively Use, and Achieving Sexual Consent

Abstract: Psychology related to areas such as gender, language, education and violence has provided scientific knowledge that contributes to reducing coercive social relationships, and to expanding freedom in sexual-affective relationships. Nonetheless, today there are new challenges that require additional developments. In the area of consent, professionals from different fields, such as law, gender, and education, are in need of evidence differentiating human communication that produces consent, and those conditions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
0
22
0
7
Order By: Relevance
“…Therefore, cultural and social discourses can be argued, and previous ideas can change, which is an important aspect of partner choice and relationships (Giordano et al, 2006). Social interactions, dialogues (Austin, 1962;Habermas, 1987;Searle, 1998), and communicative acts that include not only language but also gestures and the tone of voice as well as the social context (Searle and Soler, 2004;Flecha et al, 2020) are fundamental in transforming the processes that contribute or challenge sexual double standards. Moreover, research has already shown that communicative acts linked to NAM are decisive when preventing gender violence (Portell and Pulido, 2012;Rodríguez-Navarro et al, 2014).…”
Section: Nam Reject Perpetuating the Double Standard Through The Language Of Desirementioning
confidence: 99%
“…Therefore, cultural and social discourses can be argued, and previous ideas can change, which is an important aspect of partner choice and relationships (Giordano et al, 2006). Social interactions, dialogues (Austin, 1962;Habermas, 1987;Searle, 1998), and communicative acts that include not only language but also gestures and the tone of voice as well as the social context (Searle and Soler, 2004;Flecha et al, 2020) are fundamental in transforming the processes that contribute or challenge sexual double standards. Moreover, research has already shown that communicative acts linked to NAM are decisive when preventing gender violence (Portell and Pulido, 2012;Rodríguez-Navarro et al, 2014).…”
Section: Nam Reject Perpetuating the Double Standard Through The Language Of Desirementioning
confidence: 99%
“…This session deals with this topic using a slide presentation. This presentation includes evidence-based information on “no means no” and, more importantly, what research has shown about the need of including more than verbal communication when addressing consent, such as nonverbal acts and contexts of power relationships [45] . For example, the cases of Anna Chambers in New York who suffered rape under police custody is presented, as well as the case of La Manada in Spain.…”
Section: Resultsmentioning
confidence: 99%
“…This union between ethics and desire is not only expressed and promoted through verbal language, but also through other communicative acts such as gestures, voice tone or gaze, among others, filling egalitarian attitudes with attractiveness and desire and emptying violent behaviours from any sort of attraction (Rodríguez et al, 2014;Racionero-Plaza et al, 2020). Taking communicative acts into account is therefore essential for overcoming gender violence (Flecha et al, 2020), as it is through the various elements of communication that attraction and desire are configured.…”
Section: Construction Of the Narrative About Violence Against Womenmentioning
confidence: 99%